Parent-mediated interventions versus usual care in children with autism spectrum disorders: A protocol for a systematic review with meta-analysis and Trial Sequential Analysis. - Charlotte Engberg Conrad; Sonja Martha Teresa Ziegler; Niels Bilenberg; Jens Christiansen; Birgitte Fagerlund; Rikke Hermann Jakobsen; Pia Jeppesen; Caroline Barkholt Kamp; Per Hove Thomsen; Janus Christian Jakobsen; Marlene Briciet Lauritsen (PLoS ONE)
Introduction Autism spectrum disorder encompasses diverse patterns of social communication and repetitive, restricted behaviours. Various interventions have been developed to reduce the negative consequences of this disorder and improve levels of functioning, and recently interest in parent-mediated interventions has increased. Previous reviews and meta-analyses have investigated the effects of the parent-mediated interventions, however; a systematic review with meta-analysis of high quality has not been performed since 2013. This protocol for a systematic review with meta-analysis aims to describe the methods and purpose of synthesising current evidence regarding the effects (both positive and adverse) of parent-mediated interventions in both children with autism and their parents. Methods Electronic searches will be conducted in Cochrane Central Register of Controlled Trials (CENTRAL), Medical Literature Analysis and Retrieval System Online (MEDLINE), Excerpta Medica database (EMBASE), Latin American and Caribbean Health Sciences Literature (LILACS), American Psychological Association PsycInfo (PsycInfo) and Science Citation Index Expanded (SCI-EXPANDED). Randomised clinical trials of parent-mediated interventions for children with autism and control groups of usual care, waiting list or no treatment will be included. Two reviewers will independently screen, select and collect data. Methodological quality of included studies will be evaluated using Cochrane methodology. The primary outcome will be autism symptom severity as measured by the Autism Diagnostic Observation Schedule. Secondary outcomes will be adaptive functioning, adverse effects, child language, child´s quality of life, parental quality of life and parental stress. Meta-analyses and Trial Sequential Analysis will be performed. Discussion This is the study protocol for a systematic review and meta-analysis of parent-mediated interventions versus usual care for children with ASD. Results of the review will inform clinicians and parents about the current evidence of the effects, both positive and negative, of parent-mediated interventions on younger children with autism and their parents, through improved methodology and inclusion of new studies. PROSPERO registration number: 385188.